Developments in the Analysis of Large Antenna Arrays with Disjoint Elements - Sewraj, Keshav; Chose, Matthews; Botha, Matthys M. (2021 15th European Conference on Antennas and Propagation (EuCAP), 2021)
Efficient electromagnetic analysis of very large antenna arrays is important for various applications, including e.g., radio astronomy. The method of moments (MoM) is generally the most suitable computational electromagnetics method to deal with such open-region problems. However, its computational cost grows rapidly with problem size. This paper presents a brief overview of past work as well as the latest developments by the authors, on devising fast MoM-based methods for arrays with identical disjoint elements and arbitrary layouts. Two different lines of development are reported on, namely methods aimed at efficiently solving the full MoM system through the use of macro basis functions and adaptive cross approximation (ACA) acceleration, and a fast-converging iterative method involving localised solutions.